Initial Effect of Recombinant Human Growth Hormone Treatment in a Patient with Löwe Syndrome - Violeta Iotova; Teodora Karamfilova; Mariya Levkova; Mariya Gaydarova; Sonya Galcheva; Dimitrichka Bliznakova (MDPI AG, 2023)
Objectives: Löwe syndrome (the oculocerebrorenal syndrome of Löwe, OCRL, OMIM #309000, ORPHA: 534) is a very rare multisystem X-linked disorder characterized by ocular, kidney and nervous system anomalies. Case presentation: We present the first Bulgarian genetically confirmed patient with OCRL. The patient had facial dysmorphism, cryptorchidism, congenital cataracts, nystagmus, delayed physical and mental development, and poor nutritional status. He had severe rickets, metabolic acidosis, hypokalaemia, hypophosphataemia, and low IGF-1 levels at the age of three, in addition to his developmental delay. The molecular-genetic analysis reported a pathogenic variant c.1124A>G, p.H375R in the OCRL gene. This variant was inherited from the mother, who was a carrier. Following the diagnosis of OCRL, treatment with potassium citrate, phosphate, and calcitriol was initiated, along with an increase in caloric intake. Following general physical and biochemical improvement, therapy with rhGH started 4 years ago, and current results are presented. Conclusions: The patient with Löwe syndrome who was presented with a 6-year follow-up demonstrates the complexity of rare disease cases and the value of multidisciplinary care together with growth hormone treatment for better results in these patients.